2018
DOI: 10.29298/rmcf.v6i29.221
|View full text |Cite
|
Sign up to set email alerts
|

Estimación del carbono arbóreo en el área de manejo forestal de Ixtlán de Juárez, Oaxaca, México

Abstract: Los bosques son claves para mitigar el cambio climático global, y con un adecuado manejo pueden conciliar la producción de madera con la captura de carbono. Este estudio usó una metodología general que a partir de información del programa de manejo forestal de Ixtlán de Juárez, Oaxaca consistente en los volúmenes existentes y extraídos de pino y encino y el incremento corriente anual, permitió estimar el potencial de captura, el almacén y la dinámica del carbono en el área de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(69 reference statements)
0
4
0
2
Order By: Relevance
“…La captura de carbono forestal bajo el esquema de mercados en bosques de propiedad social está operando y tiene gran potencial, sobre todo donde se aprovecha madera a partir de la planeación y supervisión legal, técnica y social; ya que, además de seguridad en la tenencia de la tierra, se cuenta con cultura de manejo forestal (Pacheco-Aquino et al, 2015). De igual manera, Álvarez y Rubio (2013) mencionan que, aunque actualmente el principal valor del bosque de pino-encino reside en su uso como fuente de madera, el secuestro de carbono podría representar un valor adicional importante.…”
Section: Description Of Forest Development Stagesunclassified
See 2 more Smart Citations
“…La captura de carbono forestal bajo el esquema de mercados en bosques de propiedad social está operando y tiene gran potencial, sobre todo donde se aprovecha madera a partir de la planeación y supervisión legal, técnica y social; ya que, además de seguridad en la tenencia de la tierra, se cuenta con cultura de manejo forestal (Pacheco-Aquino et al, 2015). De igual manera, Álvarez y Rubio (2013) mencionan que, aunque actualmente el principal valor del bosque de pino-encino reside en su uso como fuente de madera, el secuestro de carbono podría representar un valor adicional importante.…”
Section: Description Of Forest Development Stagesunclassified
“…Forest management involves the implementation of a program of silvicultural practices, using regeneration methods and application of silvicultural practices (site preparation, clearing, pruning, thinning, protection, and promotion) that are carried out during the forest management period (Monárrez-González, Pérez-Verdín, López-González, Márquez-Linares, & González-Elizondo, 2018). Pacheco-Aquino, Durán-Medina, and Ordóñez-Díaz (2015) show signs that forests under forest management represent important carbon stores, with carbon sequestration capacity and that the sites with timber harvesting recover 15 to 20 % of the carbon removed compared to that originally present in a forest without previous interventions; these values are reached seven years after harvesting is carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could be attributed to logging that is commonly conducted in only small percentages of the community forests, with large areas dedicated entirely to conservation, particularly in larger forests. For example, in Ixtlán de Juárez, Oaxaca, one of the most successful CFEs, 71 per cent of its territory (13,792 hectares) is in conservation (Pacheco-Aquino, 2014). Cubbage et al (2015) found a lower but still substantial 28 per cent of conserved forest in a study of 30 CFEs in 12 states, with 72 per cent of the forests dedicated to timber production.…”
Section: Reducing Deforestation and Conserving Biodiversity In Mexica...mentioning
confidence: 99%
“…Ixtlán de Juárez, Oaxaca es una comunidad modelo desde el punto de vista forestal. Tiene la certificación internacional del Forest Stewardship Council (FSC) desde 2001 hasta la fecha (Pacheco-Aquino et al, 2015). También es un modelo micológico pues diversos estudios de estructura de la comunidad a nivel de esporoma se han llevado a cabo en dicha zona en los cuales el género Laccaria es de los más abundantes (Garibay-Orijel et al, 2009;Gómez-Hernández et al, 2019).…”
Section: Introductionunclassified